Platform Dakwah Media Sosial dalam Perubahan Perilaku Generasi Milenial pada Mahasiswa Fakultas Dakwah Institut Agama Islam Al-Zaytun Indonesia - Sagimin; Sobirin; Suryandari, Meity (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In the digital era, social media platforms such as Instagram, TikTok, and YouTube have become the primary sources through which the millennial generation accesses religious information quickly, conveniently, and efficiently. This development has transformed traditional preaching (da'wah) methods into more interactive forms of digital da'wah through short videos, visual content, and various communication features. However, the ease of access also presents challenges related to behavioral changes, the quality of religious understanding, and the credibility of the information received by students. This study aims to analyze the social media platforms used by students of the Faculty of Da'wah at IAI AL-AZIS to access da'wah content and to examine their influence on students' behavioral changes. The study employed a descriptive qualitative approach using purposive sampling, involving six students as research informants. Data were collected through in-depth interviews and documentation, and subsequently analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that Instagram, TikTok, and YouTube are the most frequently utilized platforms due to their accessibility, flexibility, and diverse da'wah content, including short videos, sermons, Islamic lectures, and motivational messages. The use of these platforms contributes positively to enhancing students' religious understanding, strengthening their religious attitudes, and improving their behavior, as reflected in increased discipline in worship, better moral conduct, greater ability to evaluate religious information critically, and the implementation of Islamic values in both social and academic life.